Pattern of triple negative epithelial ovarian cancer in indigenous African women [version 1; referees: 2 approved (2016)
Background: Triple negative epithelial ovarian cancer (TNEOC) refers to ovarian carcinomas that do not express estrogen receptor (ER), progesterone receptor (PR), and human epidermal growth factor receptor-type 2 (HER-2/neu). The aim of this study is to determine the pattern of triple negative epithelial ovarian cancer in indigenous African women. Methods: We performed a retrospective review of ER, PR, and HER-2/neu expression in 90 Nigerian patients with histologically diagnosed epithelial ovarian cancer. Lack of expression of ER, PR, and HER-2/neu antigens was used to determine carcinomas that are among the TNEOC. We also compared the clinicopathological parameters (age, International Federation of Gynaecology and Obstetrics (FIGO) stage, grade, and histological subtype) in patients with TNEOC and non-TNEOC. Results: Thirty-eight (42.2%) of the 90 tumours diagnosed as EOC were negative for ER, PR, and HER-2/neu expression. There was no significant association between TNEOC with other parameters such as age, FIGO stage, and histological grade. Sixteen (66.7%) of the 24 mucinous carcinomas were triple negative, while only 21 (33.3%) of the 63 serous carcinomas were triple negative, and one (50%) of the two endometrioid carcinomas was triple negative. There was a significant association between triple-negative tumours and histological subtypes of EOC (p = 0.034). Conclusions: A subtype of epithelial ovarian cancer that is negative for ER, PR, and HER-2/neu has been discovered in indigenous African women. TNEOC expression is high and is comparable to the triple negative breast cancer subtype seen in people of African ancestry. Future study of TNEOC in a large sample size should be considered.